Relationship between hydrological restoration and the recovery of vegetation communities in boreal forestry‐drained peatlands - Elo, Merja; Isoaho, Aleksi; Korhonen, Petra; Marttila, Hannu; Ovaskainen, Otso; Päkkilä, Lassi; Rana, Parvez; Räsänen, Aleksi (Wiley-Blackwell, 2025)
1.Ecosystem restoration benefits biodiversity but restoration outcomes can vary widely. In forestry-drained boreal peatlands, the limited success in restoration may arise from inadequate restoration of hydrological characteristics, most importantly water-table (WT) level. 2. We study (1) if the restoration effect on vascular plant and moss species communities is explained by WT level of restored sites, and (2) whether species groups predictions can be improved by using information on WT and nitrogen (N) levels. We use data on species communities, WT level and porewater quality before restoration and 2, 5 and 10 years after restoration from 24 restored and 16 pristine boreal peatland sites in Finland. 3. Ten years after hydrological restoration, 70% of the variation in the restoration effect for species communities was explained by the median mid-summer WT level of 2–5 years after restoration, peatland type and their interaction. 4. Species group predictions were not consistently improved by WT or N levels. 5. Synthesis and applications. The mid-term (2–5 years after restoration) WT level can be used to assess whether hydrological restoration has been successful. A minimum mid-summer WT level should be at least −25 cm from the peatland surface. A sufficient WT level is more likely to be gained in rich peatland types than in poor peatland types, and even with adequate WT level, poor sites have lower probability of positive restoration effects. Hence, rich site types could be prioritized in restoration planning.
Keywords: joint species distribution models; mire; moss; porewater quality; vascular plant; wetland; WTdepth